2018
DOI: 10.1053/j.semperi.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of the ductus arteriosus: Comparison of rodent microarrays and human RNA sequencing

Abstract: DA closure is crucial for the transition from fetal to neonatal life. This closure is supported by changes to the DA's signaling and structural properties that distinguish it from neighboring vessels. Examining transcriptional differences between these vessels is key to identifying genes or pathways responsible for DA closure. Several microarray studies have explored the DA transcriptome in animal models but varied experimental designs have led to conflicting results. Thorough transcriptomic analysis of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 78 publications
(99 reference statements)
2
25
0
Order By: Relevance
“…We evaluated the activity of VU0071063 on Kir6.2/SUR1 and Kir6.1/SUR2B channels heterologously expressed in HEK-293 cells, as well as on native Kir6.1/ SUR2B expressed in ductus arteriosus vessels. They were chosen for these studies because they are enriched in vascular K ATP channels composed of Kir6.1 and SUR2B (Shelton et al, 2014;Yarboro et al, 2018). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the activity of VU0071063 on Kir6.2/SUR1 and Kir6.1/SUR2B channels heterologously expressed in HEK-293 cells, as well as on native Kir6.1/ SUR2B expressed in ductus arteriosus vessels. They were chosen for these studies because they are enriched in vascular K ATP channels composed of Kir6.1 and SUR2B (Shelton et al, 2014;Yarboro et al, 2018). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pressure Myography. Ductus arteriosus (DA) vessels, which are enriched in Kir6.1/SUR2B channels (Shelton et al, 2014;Yarboro et al, 2018), were isolated from term-gestation fetal mice and mounted on glass pipette tips submerged in microvessel perfusion chambers as previously reported (Reese et al, 2009;Pfaltzgraff et al, 2014;Hooper et al, 2016). Chambers were placed on inverted microscopes equipped with IonOptix digital image capture and dimensioning software.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of transcriptional profiling in the rodent and human DA in comparison to the aorta demonstrated that a higher expression of EP4 was observed commonly in the rodent and human DA. 41 The differential EP4 expression was observed in mice and humans at embryonic day 14 and 21 weeks of gestation, respectively, 25 , 41 and EP4 expression increases toward term. 9 , 25 , 42 , 43 The present study identified fibulin-1 as the gene regulated by EP4 signaling, and fibulin-1 expression may be upregulated in accordance with that of EP4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…43 We further examined the expression of t-PA in human DA. 43 Although RNA sequencing of the human DA was recently reported, 46 there has been no transcriptional profiling of the human DA intimal thickening region that contains DA endothelial cells. We collected human DA from neonatal patients with congenital heart disease and examined the expression of t-PA in the intimal thickening region compared with the tunica media.…”
Section: Expression Of T-pa In Da Endothelial Cellsmentioning
confidence: 99%